“The Legend of Captain Michael Grass”: The Logic of Elimination and Loyalist Myth-making in Upper Canada, 1783-84 - Esford, Avery (Ontario History, 2023)
This article examines the founding myth for the community of Kingston, Ontario which holds that Associated Loyalist Michael Grass founded the city after he led eight companies of refugees from New York to Cataraqui (Kingston) in 1783-84. The legend is a “settler society fiction”, an invented founding narrative that privileges Loyalist history at the expense of other communities including the Indigenous Mississauga. Comparing the legend and documents from Grass’s lifetime, shows that the Indigenous presence at Cataraqui has been effectively eliminated. The legend justifies the dispossession of the local Mississauga, accounts for the sudden presence of White settlers on the north shore of Lake Ontario, and perpetuates a settler society fiction.